Treatment of myositis ossificans progressiva with a diphosphonate. - Russell, R; Smith, R; Bishop, M; Price, D (1972)
The diphosphonate, disodium etidronate (ethane-1-hydroxy-1,1-diphosphonate, 'EHDP'), a compound known to inhibit the crystal growth of hydroxyapatite and to prevent ectopic calcification in experimental animals, has been given to two women with myositis ossificans progressiva. After removal of ectopic bone during treatment with disodium etidronate there was no X-ray evidence of significant recalcification six months later in one patient, and a year later in the other. On previous occasions removal of ectopic bone had been followed by rapid recurrence at the site of operation. © 1972.